Health Care Expenditures in OECD Countries : A Panel Unit Root and Cointegration Analysis - Christian Dreger; Hans-Eggert Reimers (Institute for the Study of Labor (IZA), 2005)
This paper investigates the link between health care expenditures and GDP for a sample of 21 OECD countries using recent developed panel cointegration techniques. In contrast to previous studies, the analysis accounts for the fact that health care expenditures are not only determined by income. The other driving force is medical progress, which is proxied by different variables, like life expectancy, infant mortality and the share of the elderly. In the extended models, a cointegration relationship can be established among the variables. The income elasticity is not different from unity, implying that health care expenditures are not a luxury good. This finding is robust for alternative measures of medical progress. The evidence is unchanged, if alternative estimators of the cointegration vector are used. Controlling for cross section dependency does not affect the principal results, as cointegration can be found even in a model among nonstationary common factors.
Keywords: I10; C23; 330; health care expenditures; medical progress; panel cointegration; Gesundheitskosten; Wirtschaftswachstum; Medizin; Technischer Fortschritt; Sterblichkeit; Schätzung; OECD-Staaten